Characterization of the shape memory effect in natural biopolymers - Ji, Peng Yuan (2018)
Shape Memory polymers are the class of polymer which has ability to return to their original shape by external stimuli [6]. Shape memory polymers are very responsive to water, temperature and heat. Experimental results fully support the hypothesis. Feeler of shrimp is considered a Natural Bio-polymer shows response to water and heat and are able to get original shape. Feelers of shrimp respond to the external stimulus. In this experimental setup, heat response and water response is determined. Initially feelers were shaped into different types using specific shaping tools. Six sets of shaped and dried feelers were exposed to external stimulus. Each two of six sets were dried by naturally with room temperature, heating by oven with 12mins in 100deg and dry by hairdryer with blowing in room temperature. Afterwards one of two set was soaked in normal water while another set was soaked in hot water. Few sets have recovered its original shape after two hours while the rest of sets could not recovered its shape even after two hours minutes. Few sets shows the effect of heating system and hot water which contains high energy. The heating system and hot water shall cause the changes in internal structure of feeler. Transformation of internal structure restricted the conversion to original shape. The detail experiment procedures and conclusion will be presented in next chapters of the report.